Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1086/368247
|View full text |Cite
|
Sign up to set email alerts
|

Wing Near-Infrared, TiO-Band, andV-Band Photometry of Chromospherically Active Star Andromedae

Abstract: As a pilot program, Wing near-IR, TiO-band, and V-band photometry is being conducted of the RS Canum Venaticorum type, chromospherically active, G8 IV-III star Andromedae. The objective is to investigate a possible relationship between variation of the $54 day rotationally starspot modulated visual light curve and TiO absorption strength. The TiO ( , 0, 0) absorption band strength at = 719 nm is very sensitive to temperature for cool stars and manifests itself in cooler starspot regions (T 4000 K). TiO photome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Since giant stars have extended chromospheres, these velocities become comparable to the stellar escape velocity, and can be said to mark the presence of a stellar wind. At the time when we observed the He i 10 830 Å line in λ And, Mirtorabi et al (2003) monitored the star searching for periodicity in visible light and in photospheric spot coverage. During the period of our NOT observations of λ And, no important changes occurred in the observations of Mirtorabi et al (2003), and the He i λ10 830 did not show substantial changes in strength either.…”
Section: Resultsmentioning
confidence: 99%
“…Since giant stars have extended chromospheres, these velocities become comparable to the stellar escape velocity, and can be said to mark the presence of a stellar wind. At the time when we observed the He i 10 830 Å line in λ And, Mirtorabi et al (2003) monitored the star searching for periodicity in visible light and in photospheric spot coverage. During the period of our NOT observations of λ And, no important changes occurred in the observations of Mirtorabi et al (2003), and the He i λ10 830 did not show substantial changes in strength either.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some authors have found that for the less active stars the variability at the optical wavelengths is significantly influenced by faculae, if not quite dominated, e.g. Mirtorabi et al (2003), Radick et al (1990Radick et al ( , 1998, while for the most active stars the effect of starspots dominates and faculae are not required to obtain quite satisfactory light curves models (e.g. Henry et al 1995;Lanza et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The TiO‐band strengths obtained by O'Neal et al (2004) in 1998 seem to be showing the expected anticorrelation with the visual brightness of DM UMa. Mirtorabi, Wasatonic & Guinan (2003) have reported that in the long‐period RS CVn binary λ And the TiO‐band strengths measured using narrow‐band filters show the expected anticorrelation only at certain observing seasons and that the same is probably true for the active RS CVn binary II Peg. In connection with the lack of anticorrelation at all times, O'Neal et al (2004) have pointed out the possible inadequacy of the two‐component model of RS CVn stars consisting of only the unspotted and spotted photospheric regions.…”
Section: Discussionmentioning
confidence: 90%